2019
DOI: 10.1016/j.respol.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

“All for One and One for All?” - Knowledge broker roles in managing tensions of internal coopetition: The Ubisoft case

Abstract: Coopetition, i.e., cooperation between competing actors, has become a pervasive strategy for innovative firms. The primary focus of studies investigating coopetition centers on inter-firm relationships, highlighting the benefits, limits and configurational patterns of cooperative relationships between competing firms. Only a small, emerging group of studies seeks to extend the concept to the intra-firm level, stressing the existence and effects of competition and cooperation between units that are part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 132 publications
1
69
0
5
Order By: Relevance
“…However, pursuing the contradictory exploration and exploitation activities simultaneously could make the trade-off of ambidexterity challenging for firms (Gibson and Birkinshaw, 2004), due to the potential tensions such as trade-offs between pursuing one activity over the other (Gibson andBirkinshaw, 2004, Simsek et al, 2009). With the knowledge routines in place, firm's managers, as knowledge brokers, can differentiate the simultaneous activities (Chiambaretto et al, 2019), and deal with the trade-offs in relationships as per the firm's intent. Accordingly, scholars argue that when strategic intent is complemented by knowledge flows, managers can think and act ambidextrously for their firm to attain exploration and exploitation objectives simultaneously Wong, 2004, Gibson andBirkinshaw, 2004), with better coordination and strategic control (Veliyath, 1992, Bodwell and Chermack, 2010, O'Reilly lll and Tushman, 2011.…”
Section: H3: Manager's Ambidexterity Is Positively Associated To Coopmentioning
confidence: 99%
See 2 more Smart Citations
“…However, pursuing the contradictory exploration and exploitation activities simultaneously could make the trade-off of ambidexterity challenging for firms (Gibson and Birkinshaw, 2004), due to the potential tensions such as trade-offs between pursuing one activity over the other (Gibson andBirkinshaw, 2004, Simsek et al, 2009). With the knowledge routines in place, firm's managers, as knowledge brokers, can differentiate the simultaneous activities (Chiambaretto et al, 2019), and deal with the trade-offs in relationships as per the firm's intent. Accordingly, scholars argue that when strategic intent is complemented by knowledge flows, managers can think and act ambidextrously for their firm to attain exploration and exploitation objectives simultaneously Wong, 2004, Gibson andBirkinshaw, 2004), with better coordination and strategic control (Veliyath, 1992, Bodwell and Chermack, 2010, O'Reilly lll and Tushman, 2011.…”
Section: H3: Manager's Ambidexterity Is Positively Associated To Coopmentioning
confidence: 99%
“…Second, while previous studies discuss potential relationships between ambidextrous managers and various paradoxical activities inherent to coopetition (Luo, 2007b, Bengtsson et al, 2016a, Estrada and Dong, 2019, Chiambaretto et al, 2019, Bouncken et al, 2020, they lack clarity in explaining what skillsets could make managers ambidextrous. Additionally, extant research has also overlooked the potential direct relationship between ambidextrous managers and coopetition.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…been shown that third parties can act as knowledge brokers facilitating management of tensions in internal coopetition (Chiambaretto, Massé, & Mirc, 2019) or as trust builders supporting the implementation of network coopetition (Porto Gomez, Otegi Olaso, & Zabala-Iturriagagoitia, 2016). Moreover, trust complements contractual complexity and dependency (Ratzmann et al, 2016) facilitating the implementation of plural governance, which has found to favour coopetition and improve innovation performance (Bouncken et al, 2016).…”
Section: Chiambaretto Et Al (2019)mentioning
confidence: 99%
“…If coopetition is most often studied at an inter-organizational level, i.e. between coopetitors, it also has consequences at the intraorganizational level, between business units competing for internal resources or external markets (Chiambaretto et al, 2019). Scholars have therefore investigated several dimensions and levels of coopetition, but very little has been discussed about the feelings of individuals inside organizations that engage in coopetition.…”
Section: Coopetition: An Increasingly Rigorous and Relevant Theoreticmentioning
confidence: 99%